Cost of Production for Processed Oranges in Southwest Florida in 2020/21 - Ariel Singerman (EDIS)
This article presents a summary of the 2020/21 costs of production for processed oranges grown in southwest Florida. The methodology chosen to collect the data consisted of surveying growers directly so as to reflect their costs. The total cost of production for processed oranges in 2020/21 was $1,882.43 per acre. Typical users of these estimates include growers and consultants, who use them as a benchmark; property appraisers, who use them to compute the taxes for property owners; and researchers, who use the estimates to evaluate the economic feasibility of potential new technologies.